2016
DOI: 10.1177/0963662516636040
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of trust in the general science and climate science research of US federal agencies

Abstract: In this article, we focus on a key strategic objective of scientific organizations: maintaining the trust of the public. Using data from a nationally representative survey of American adults ( n = 1510), we assess the extent to which demographic factors and political ideology are associated with citizens' trust in general science and climate science research conducted by US federal agencies. Finally, we test whether priming individuals to first consider agencies' general science research influences trust in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 46 publications
2
55
0
4
Order By: Relevance
“…Indeed, past research has found that both liberals and conservatives are susceptible to motivated distrust of scientific information that is incongruent with their ideology or worldview (Kahan, Jenkins-Smith, & Braman, 2011;Nisbet, Cooper, & Garrett, 2015). With regard to the issue of climate change, these studies and others find that conservatives tend to be less trusting of climate science compared to liberals (Kahan et al, 2011;McCright & Dunlap, 2011;Myers et al, 2016;Nisbet et al, 2015). However, these past studies did not test stimuli that differentiate public responses to statements from scientists that contain explicit endorsements of solutions to address climate change from statements that do not contain such endorsements.…”
Section: Introduction and Contextmentioning
confidence: 92%
“…Indeed, past research has found that both liberals and conservatives are susceptible to motivated distrust of scientific information that is incongruent with their ideology or worldview (Kahan, Jenkins-Smith, & Braman, 2011;Nisbet, Cooper, & Garrett, 2015). With regard to the issue of climate change, these studies and others find that conservatives tend to be less trusting of climate science compared to liberals (Kahan et al, 2011;McCright & Dunlap, 2011;Myers et al, 2016;Nisbet et al, 2015). However, these past studies did not test stimuli that differentiate public responses to statements from scientists that contain explicit endorsements of solutions to address climate change from statements that do not contain such endorsements.…”
Section: Introduction and Contextmentioning
confidence: 92%
“…"Trust" is, of course, an ambiguous term which can refer to at least two different kinds of attitudes and consequently generate two distinct, but in practice often overlapping, aims of science communication. It is useful here to distinguish between epistemic trust and moral trust (for a similar distinction see e.g., Borchelt, 2008;Earle, 2010;Fiske and Dupree, 2014;Myers et al, 2017). As we understand it, an individual has epistemic trust in a scientific institution when the individual is strongly inclined to believe that what the institution communicates as true and epistemically justified, unless the individual is exposed to salient defeaters, that is, specific reasons to or evidence suggesting that institution in question is not trustworthy.…”
Section: A Conceptual Framework Of Science Communication Aimsmentioning
confidence: 99%
“…(3) Generation of public epistemic and moral trust. While numerous studies have been conducted to assess the public's levels of epistemic and moral trust in science in general (e.g., Besley, 2014), and regarding specific areas of research and scientists and scientific institutions (e.g., Myers et al, 2017), the question of what factors mediate and promote trust is just beginning to be uncovered (e.g., Nisbet and Scheufele, 2009;Fiske and Dupree, 2014;Nadelson et al, 2014;Hendriks et al, 2016c;Myers et al, 2017). Consequently, despite the aim of promoting epistemic and moral trust arguably being widely endorsed in the public participation paradigm (see e.g., Dietz, 2013), the research on whether communicative efforts are in fact promoting these aims is limited.…”
Section: Do Various Models Of Science Communication Achieve the Aims?mentioning
confidence: 99%
“…Earning and maintaining public trust is pivotal for scientists and institutions communicating with the public (Myers et al, 2016;Poortinga & Pidgeon, 2003). Perceived consensus is one dimension on which the public judge experts, sometimes with serious consequences.…”
Section: When Experts Change and Disagreementioning
confidence: 99%